GENDER-DISTINGUISHING LEXEMAS - Ismoilova Dilrabo Muhammad qizi (Modern American Journals, 2025)
This article investigates gender-differentiated lexemes in the Uzbek language within the framework of sociolinguistics and gender linguistics. The study examines how lexical items reflect and reinforce gender distinctions in social, cultural, and communicative contexts. It emphasizes that language serves as both a mirror and a mechanism of gender perception, encoding societal attitudes, roles, and stereotypes. Through comparative, semantic, and pragmatic analyses, the research identifies linguistic markers that convey gender differentiation, explores their etymological roots, and evaluates their transformations in modern usage. The findings reveal that gender-differentiated lexemes not only shape linguistic expression but also influence the construction of gender identity and the reproduction of cultural norms in discourse.
Keywords: Gender linguistics, gender-differentiated lexemes, sociolinguistics, lexical semantics, gender stereotypes, language and culture, discourse analysis, Uzbek language.